PERAN MASYARAKAT TERHADAP KONSERVASI DAERAH ALIRAN SUNGAI (DAS) BAGIAN HILIR DESA NOELMINA KECAMATAN TAKARI KABUPATEN KUPANG - Saefatu, Jack F; Rahmawati, Arfita (Universitas Nusa Cendana, 2023)
This study aims to: (1) Knowing the utilization used by the people of Noelmina Village on the Noelmina Watershed; (2) find out about the Conservation (DAS) carried out by the Noelmina Village community towards Noelmina's (DAS. The study used a qualitative method with 20 informants living on the Noelmina river border by using a snowball sampling technique. Sources consist of primary and secondary data collected by observation, interviews and documentation. The results of the analysis in the study show that: (1) The Noelmina Village community utilizes the Noelmina Watershed (DAS) to support their life activities including agriculture, animal husbandry, daily needs and mining.; (2) Conservation carried out by the Noelmina community as well as those carried out by the government and private parties include planting trees in river border areas, making terraces in river border areas, making gabions and directing water flow.